Emission properties of YAG: Ce ceramics with barium fluoride flux; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Stepanov S. A. Sergey Aleksandrovich; Valiev D. T. Damir Talgatovich; Vaganov V. A. Vitalii Andreevich; Shrayber A. M.; Paygin V. D. Vladimir Denisovich (2021, 2021)
Title screen